FAKTOR-FAKTOR YANG MENARIK MINAT WISATAWAN DOMESTIK BERKUNJUNG KE PANTAI PANDAWA - I Nyoman Meirejeki; I Ketut Suarta; Md Abdi Sucipta (Soshum: Jurnal Sosial dan Humaniora, 2014)
The research was inspired by the increasing number of competition among Tourist Destination or DTW in Badung because nearly all areas have a beautiful nature, a remarkable cultural heritage, and hospitality of its people is quite a potential tourist attraction. Badung has the potential diverse tourist attractions, agro tourism in the North and beach tourism in the Southern areas. Pandava beach is one of the tourist areas in the village of Kutuh. The purpose of this research are to investigate what factors are considered by tourists visiting the Pandava Beach and Which is the most dominant Factor into consideration of domestic tourists visiting the Pandava Beach. The determination of the criteria of research from respondents uses a Likert scale to measure the nature, the opinions and perceptions of a person or a group of people about a social phenomenon with a number of sample as many as 85 people. Analytical tool used in this study is the analysis of the factor with the help of SPSS version. 17. From the test results of the four factors influencing tourists to visit the Pandavas Beach: beach beauty and strategic location, which is composed of natural beaches, recreational facilities, recreational facilities and the condition of its strategic location; Price and access to the beach Pandavas, which consists of the price of food and beverages, recreation rents, large parking area, access to which is smooth, safe and friendly community; Responsiveness and hygiene, the variables that make up the service guides are good, responsive coast guard, coastal environmental hygiene; Promotions and services, which consists of a variable where to eat in coastal areas, promotion and service personnel, it was found that the most dominant factor affecting the interest of tourists to visit the beach Pandavas are factors beach beauty and strategic location. It can be seen from the eigenvalues value equal to 7.704 which is the highest value of the total value of eigen value.